Attentional focus effects on sprint start performance as a function of skill level - Ille, A.; Selin, I.; Do, M.-C.; Thon, B. (Journal of Sports Sciences, 2013)
Several researchers have demonstrated that an external focus of attention (about movement`s effects) during movement execution allowed better performances and learning of various motor tasks than an internal focus of attention (about movement itself). However, attentional focus effects have not been studied in tasks requiring explosive actions preceded by fast reaction time to a signal, such as a sprint start. We hypothesised that the beneficial effect of external focus of attention would be observed in the different stages of the sprint start (i.e. reaction time, block clearance and running) for both expert and novice sprinters. Novice and expert sprinters performed sprint starts followed by a 10 m sprint under three conditions: external focus instructions; internal focus instructions; and neutral instructions. The reaction time and the running time were significantly shorter in the external focus condition than in the internal focus condition, for both expert and novice participants. These results confirm the beneficial effect of an external focus of attention on the speed of movement execution. Moreover, they revealed that attentional focus influences movement preparation. Several hypotheses are proposed to account for these results, with reference to the processes that could be responsible for the observed effects.